2015
DOI: 10.1074/jbc.m115.668160
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Target the Leukemic Microenvironment by Enhancing a Nherf1-Protein Phosphatase 1α-TAZ Signaling Pathway in Osteoblasts

Abstract: Disrupting the protective signals provided by the bone marrow microenvironment will be critical for more effective combination drug therapies for acute myeloid leukemia (AML). Cells of the osteoblast lineage that reside in the endosteal niche have been implicated in promoting survival of AML cells. Here, we investigated how to prevent this protective interaction. We previously showed that SDF-1, a chemokine abundant in the bone marrow, induces apoptosis of AML cells, unless the leukemic cells receive protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 52 publications
3
24
0
1
Order By: Relevance
“…First of all, we found that the hypoxia marker, HIF-1α, which in human PDAC samples correlates with tumor size, aggressiveness and poor prognosis (26), exhibited the lowest protein levels in the 2D system and the highest expression in both Matrigel cultures exposed to EGF and in the organotypic cultures even in the absence of EGF. This expression pattern, which reflects the desmoplastic, hypovascularised and highly hypoxic nature of PDAC only in the organotypic model, was shared by another tumor hypoxia microenvironment-associated protein (27)(28)(29)(30), the scaffolding protein NHERF1. Importantly, NHERF1 expression is also increased in several human cancers including PDAC (10) and it can be phosphorylated by the protein kinase A (PKA), via the PKA-anchoring activity of ezrin (31).…”
Section: Resultsmentioning
confidence: 83%
“…First of all, we found that the hypoxia marker, HIF-1α, which in human PDAC samples correlates with tumor size, aggressiveness and poor prognosis (26), exhibited the lowest protein levels in the 2D system and the highest expression in both Matrigel cultures exposed to EGF and in the organotypic cultures even in the absence of EGF. This expression pattern, which reflects the desmoplastic, hypovascularised and highly hypoxic nature of PDAC only in the organotypic model, was shared by another tumor hypoxia microenvironment-associated protein (27)(28)(29)(30), the scaffolding protein NHERF1. Importantly, NHERF1 expression is also increased in several human cancers including PDAC (10) and it can be phosphorylated by the protein kinase A (PKA), via the PKA-anchoring activity of ezrin (31).…”
Section: Resultsmentioning
confidence: 83%
“…4C). Prior work first identified NHERF1 binding to PP1␣ but did not disclose a binding site (52). PP1 lacks a C-terminal PDZ sequence, suggesting that it did not bind NHERF1 through a canonical PDZ-ligand recognition motif.…”
Section: Discussionmentioning
confidence: 94%
“…We first directed our attention at identifying the phosphatase responsible for the rapid Ser 290 dephosphorylation. Our interest centered on PP1␣ because it was shown to bind NHERF1 (52) and was found here to be among the most frequent interacting NHERF1 partners (Table S1). Mass spectrometry analysis of pulldown samples revealed 10 unique PP1␣ peptides with greater than 45% sequence coverage (Table S2).…”
Section: Protein Phosphatase 1␣ (Pp1␣) Binds Nherf1 and Mediates Ser mentioning
confidence: 99%
“…For NFAT localization, subcellular fractionation was performed as described. 35 The 39 untranslated region (UTR) luciferase reporter vector was generated by cloning the complete IL-2 39UTR into pmirGLO (Promega) using the following primers: 59GGCGCCGCTAGCTAATTAAGTGCTTCCCAC39 and 59GCCCGCGTC GACTTTTTTTTATATTTATCAAATTTATTAAATAGTTTTACTAACC39.…”
Section: Rac1 Activation Erk Activation Nfat Localization Luciferamentioning
confidence: 99%